The importance of underpaint corrosion caused by damage to paint on steel structures - Ribeiro Filho, Guido Lessa; Ribas, Rovadávia Aline de Jesus; Donizetti de Paula, Geraldo (Revista ALCONPAT, 2020)
The impact of varying the dry paint film thickness (DFT) on the underpaint corrosion of steel plates obtained from the floor of an offshore oil platform is evaluated. The specimens were all prepared using the same material and paint scheme, and the DFT and exposure conditions in a salt spray chamber were varied and compared with the results obtained in a real situation. The results indicated that corrosion initiated at sites where the paint was damaged, may be more important than corrosion through the undamaged paint due to permeation, even in cases where the DFT is thin. In specimens whose substrates were previously damaged, there were pathological manifestations of osmotic blistering. The underpaint corrosion that occurred after the paint was damaged in the field occurred at an intensity like that observed for the tested specimens.